(untitled) (Advances in Military Technology, 2013)
Soldiers’ fungal and bacterial infections, especially in their feet, cause significant reduction in their performance. Copper has potent antifungal and antibacterial properties. Copper is also an essential trace element vital for the normal function of skin and wound healing. Socks containing copper oxide particles, such as socks designed to protect the feet of diabetic individuals, are commercially available in many countries. This article describes the results of a trial conducted with 53 soldiers undergoing intensive basic training. The soldiers used the socks with copper oxide daily for a period of three weeks. At the end of the trial the vast majority of soldiers reported a notorious reduction in their feet skin irritation, itching, and dryness and reduction in foot and sock odour. Reduced foot infection and discomfort improves the soldiers’ physical and mental health, increases productiveness and decreases medical treatment costs and days lost for treatment. For these reasons, and in view of the results of this trial, socks containing copper oxide particles may be an important part of every soldiers’ arsenal of personal equipment.